Routledge Companion to Jane Austen - Wilson, Cheryl A.; Frawley, Maria H. (Taylor & Francis, 2022)
First published anonymously, as 'a lady', Jane Austen is now among the world's most famous and highly revered authors. The Routledge Companion to Jane Austen provides wide-ranging coverage of Jane Austen's works, reception, and legacy, with chapters that draw on the latest literary research and theory and represent foundational and authoritative scholarship as well as new approaches to an author whose works provide seemingly endless inspiration for reinterpretation, adaptation, and appropriation. The Companion provides up-to-date work by an international team of established and emerging Austen scholars and includes exciting chapters not just on Austen in her time but on her ongoing afterlife, whether in the academy and the wider world of her fans or in cinema, new media, and the commercial world. Parts within the volume explore Jane Austen in her time and within the literary canon; the literary critical and theoretical study of her novels, unpublished writing, and her correspondence; and the afterlife of her work as exemplified in film, digital humanities, and new media. In addition, the Companion devotes special attention to teaching Jane Austen.